Menumbuhkan Budaya Literasi Melalui Kecakapan Digital di Kalangan Mahasiswa Sosiologi Fakultas Ilmu Sosial dan Humaniora UIN Sunan Kalijaga Yogyakarta - Muhammad Reza Aulia Almahdi; Mumtaz Syabits Fathoni; Yayang Tri Fatmah; Zahra Salma Faidah (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2022)
This study aims to discuss two important questions related to the causes of low interest in reading for millennials and the right solution to foster millennial literacy interest in Sociology Students, Faculty of Social Sciences and Humanities, UIN Sunan Kalijaga. This research uses descriptive qualitative research method with the type of case study research. This research resulted in an answer that, The low interest in reading among students was due to several things, especially the development of digital technology. The development of digital technology if it is not balanced with self-control in its use can be detrimental to its users and can even be the main cause of the decline in literacy levels among students. However, digital technology can also be an effective stimulant that triggers an increase in reading interest. The lack of parental role in providing literacy culture is a factor that needs to be considered. Literacy interest is also influenced by the presence or absence of facilities for reading, if the facilities are complete and comfortable, it will support students' interest in reading. For some students, the pressure of the task that forces them to read a lot of literature actually becomes a fairly effective stimulant. With these factors, it is clear how the interest in literacy among students is, there are some students whose literacy awareness is still low. However, this can be overcome by providing effective and appropriate stimulants for them.Keywords: Digital Literacy, Digital Skills, Literacy Culture.